Clinical inertia among patients with type 2 diabetes mellitus treated with DPP-4i and/or SGLT-2i. (December 2018) - Lanzinger, S.; Schmid, S.M.; Welp, R.; Zimmermann, A.; Fasching, P.; Wagner, S.; Holl, R.W.
Abstract: Objectives: Failure to intensify treatment of patients with type 2 diabetes (T2D) in a timely manner is a common challenge. If newer oral anti-diabetic drugs (NOADs) such as dipeptidyl peptidase-4 inhibitors (DPP-4i) and sodium/glucose cotransporter 2 inhibitors (SGLT-2i) do not achieve metabolic control, injectable therapy like insulin or glucagon-like Peptide 1 (GLP-1) receptor agonists are required. We investigated the time in poor glycaemic control (PC, HbA1c > 7%, >7.5%, >8%) in adults with T2D treated with DPP-4i/SGLT-2i until treatment intensification with insulin/GLP-1 or until the most recent documented visit. Methods: T2D ≥ 18 years were identified from the diabetes patient follow-up registry (DPV), which captures data from diabetes specialist care. Patients with ≥2 documented visits with DPP-4i/SGLT-2i treatment and with the most recent treatment year ≥2015 were included. Results: The study population consisted of 4576 patients treated with DPP-4i/SGLT-2i. A subgroup of 1416 patients were intensified with an injectable therapy. Mean time in PC until intensification with insulin/GLP-1 was 16.7 months (HbA1c > 7%), 15.7 and 15.1 months (HbA1c > 7.5%, HbA1c > 8%) in this subgroup, respectively. Mean time in PC until most recent visit was 12.6, 9.9 and 8.4 months in the subgroup of patients without treatment intensification. Conclusions: Even with NOADs, a substantial proportion of T2D do not achieve good metabolic control. These findings may be due to individualized target setting for HbA1c, or reluctance of patients and physicians towards injectable therapy. Effective diabetes management strategies are necessary to reduce the risk of adverse outcomes and to increase quality of life in T2D.